Thermal expansion of (MnIn2S4)1-x•(AgIn5S8)x solid solutions - Chan Bin Tkhan; I. V. Bodnar (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The thermal expansion of single crystals of solid solutions (MnIn2S4)1–х•(AgIn5S8)х was measured by the dilatometric method in the temperature range 80–450 K. The coefficients of thermal expansion are determined and their concentration dependences at different temperatures are constructed. It is established that the indicated quantities with composition x vary linearly. From the obtained values of the coefficients of thermal expansion, the Debye temperatures and the mean-square dynamic displacements of the atoms are calculated. It is shown that as the temperature is raised, the Debye temperature decreases, and the mean square dynamic displacements of the atoms increase.